Botucatu: modernização e infraestrutura urbana no interior paulista (1928-1934) - Botaro, Luís Gustavo Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The São Paulo's inland cities modernizations, among the last decades of the nineteenth century and the first decades of the twentieth century, is concurrent with the large Brazilian cities renovations, as Rio de Janeiro, São Paulo and Santos. Since the economic and demographic growth generated by the coffee-growing culture and the raiway presence, some of São Paulo's inland cities suffered changes and renovations. Our research aims to investigate the image of the city of Botucatu between 1928 and 1934. In those years, the newspapers (Correio de Botucatu, Jornal de Notícias e Folha de Botucatu) were discussing urban improvements that were necessary to the urban modernization, such as the paving of the streets, the extension of water distribution services, the aestethics of private and public space as well as a concern with society's habits and behavior. During this period there were also reforms and extensions of the city's railway infrastructure, like the constructions of mechanical workshops, expansion of warehouses and the station's building renovation. This research aims to investigate what the Socoraba Railway and the longed urban improvements meant, from the aegis of modernization, using the Botucatu's newspapers and the railroad company's reports as source

O processo de modernização das cidades do interior paulista, entre as últimas décadas do século XIX e primeiras do XX, é concomitante com as reformas dos grandes centros brasileiros, como Rio de Janeiro, São Paulo e Santos. A partir do crescimento demográfico e econômico gerado pela cultura cafeeira e pela presença da ferrovia, alguns municípios do interior paulista foram palcos de mudanças e reformas. Nossa pesquisa tem como objetivo geral investigar a imagem acerca da cidade de Botucatu, entre os anos de 1928 a 1934. Naqueles anos, os jornais (Correio de Botucatu, Jornal de Notícias e Folha de Botucatu) discutem melhoramentos urbanos necessários à modernização do espaço urbano, como o calçamento das ruas, ampliação dos serviços de distribuição de água, a estética dos espaços públicos e privados, bem como, uma preocupação com os hábitos e costumes da sociedade. Nesse período ocorreram também reformas e ampliações das estruturas ferroviárias da cidade colocadas em prática pela Estrada de Ferro Sorocabana, como a construção de oficinas, ampliação dos armazéns e a reforma do prédio da estação. Em síntese, nossa pesquisa tem como objetivo geral investigar qual a imagem acerca da cidade de Botucatu, a partir da égide da modernização, utilizando como fonte os jornais de Botucatu e os relatórios da companhia ferroviária
Keywords: Ferrovias; Transporte ferroviario; Botucatu (SP); Railroads